2011
DOI: 10.1111/j.1559-1816.2011.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anxiety, Disaster Education, and Resources on Disaster Preparedness Behavior

Abstract: The thrust of this study is to understand the responses of anxiety‐prone people to threats like natural disasters. It examines whether anxiety influences disaster preparedness, and whether disaster education and resources mediate between anxiety and disaster preparedness. Data were collected from 300 people, each from flood‐prone and heat‐wave‐affected areas in Orissa, India. Controlling for the influence of age and family type, the results revealed that trait anxiety decreased flood and heat‐wave preparedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 28 publications
7
54
0
2
Order By: Relevance
“…Such heightened anxiety vulnerability is associated with a range of dysfunctional outcomes. Trait anxiety is also negatively associated with natural hazard preparedness in individuals living in areas prone to floods, heatwaves, or earthquakes (de Man & Simpson-Housley, 1988;Mishra & Suar, 2012;Paton, Smith, & Johnston, 2005). Evidence from the field of health psychology further suggests that heightened anxiety vulnerability is associated with poorer engagement in health protection and disease prevention.…”
Section: What This Topic Adds?mentioning
confidence: 99%
See 2 more Smart Citations
“…Such heightened anxiety vulnerability is associated with a range of dysfunctional outcomes. Trait anxiety is also negatively associated with natural hazard preparedness in individuals living in areas prone to floods, heatwaves, or earthquakes (de Man & Simpson-Housley, 1988;Mishra & Suar, 2012;Paton, Smith, & Johnston, 2005). Evidence from the field of health psychology further suggests that heightened anxiety vulnerability is associated with poorer engagement in health protection and disease prevention.…”
Section: What This Topic Adds?mentioning
confidence: 99%
“…Some researchers have suggested that anxietylinked impairments in preparedness for potential danger may be the result of biased attentional processes known to be associated with anxiety (Duval & Mulilis, 1999;Mishra & Suar, 2012). Some researchers have suggested that anxietylinked impairments in preparedness for potential danger may be the result of biased attentional processes known to be associated with anxiety (Duval & Mulilis, 1999;Mishra & Suar, 2012).…”
Section: What This Topic Adds?mentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety-prone persons do not show adaptive responses in crises because of their emotional distress. They think that the person in position of authority will take care of them in crises (Mishra and Suar 2012). Furthermore, following the ancient scriptural lessons, most Indians have learnt to practise serenity in thinking and action (Suar 2013), and to be non-anxious.…”
Section: Self-enhancement Cognitive Biasmentioning
confidence: 99%
“…Џонсон (Johnson еt al., 2014) у раду указује да постоји позитивна корелација између спремности домаћинства и учешћа деце у образовним програмима о катастрофама. Мишра и Суар (Mishra & Suar, 2012) указују да су образовање о катастрофама и ресурси делимични посредници између анксиозности и спремности за поплаве и главни посредници између анксиозности и спремности за топлотне таласе. Ронан и сарадници (Ronan, Crellin & Johnston, 2012) у раду потврђују значајну улогу образовних програма о опасностима у подизању нивоа спремности домаћинства за катастрофе.…”
Section: утицај демографских социоекономских и психOлошких карактериunclassified